Novel molecular markers for Taxodium breeding from the chloroplast genomes of four artificial Taxodium hybrids - Yue, Minghua; Chen, Hong; Xuan, Lei; Yang, Ying; Chong, Xinran; Li, Mingzhi; Yu, ChaoGuang; Lu, Xiaoqing; Zhang, Fan (Frontiers in Genetics, 2023)
Taxodium 'Zhongshanshan' are a group of intraspecific Taxodium hybrids with superparental dominance and high ecological and economic value in southern China. Identifying the parentage of hybrids, especially the male parent, is critically important for genetic studies. However, the large nuclear genomes of members of the genus Taxodium pose a major challenge for the development of molecular markers. Here, we developed novel molecular markers by conducting a comparative analysis of the chloroplast genomes of four artificial Taxodium hybrids and their parents. The lengths of the whole chloroplast genome ranged from 131,942 to 132,128 bp; the total guanine (GC) content of the chloroplast genomes ranged from 34.6% to 35.81%. A total of 120 unique genes were identified, including 83 protein-coding genes, 33 transfer RNAs, and four ribosomal RNAs. A total of 69-71 simple sequence repeats were detected in the four hybrids. Phylogenetic analysisrevealed that these hybrids clustered with their paternal parents. Similar findings were obtained based via analysis of the GC content of protein-coding genes. Molecular markers were developed using the highly variable regions of the chloroplast genomes, and polymerase chain reaction (PCR) assays revealed that these markers were effective for identifying the male parents of these hybrids. Our findings indicate for the first time that the chloroplast genomes of Taxodium are paternally inherited.Generally, these molecular markers could facilitate breeding and genetic studies of Taxodium.